Legal Protection for Investors in Case of Stock Fraud in the Capital Market - Neni Anggraeni; Dudik Djaja Sidarta; Renda Aranggraeni; Siti Marwiyah; Bachrul Amiq (Journal of International Multidisciplinary Research, 2025)
The Indonesian capital market plays a pivotal role in mobilising long-term financing for corporations and providing investment opportunities to the public. However, persistent stock fraud cases undermine market integrity and investor confidence. This study aims to evaluate the effectiveness of the existing legal framework for investor protection against stock fraud, analyse its practical implementation, and recommend measures to strengthen both preventive and repressive mechanisms. Employing a normative legal research design with a qualitative approach, the study integrates statute, conceptual, and case approaches, focusing on Law No. 8 of 1995 on Capital Markets, OJK regulations, the Criminal Code, and notable cases such as PT Hanson International Tbk. The findings reveal that while the legal framework normatively aligns with the Legal Protection Theory, Justice Theory, and Legal Effectiveness Theory, substantial gaps remain between regulation and enforcement. Weak supervisory coordination, delayed intervention, lengthy judicial processes, and low investor legal literacy reduce effectiveness. Recommended reforms include adopting regtech and suptech, enhancing cross-agency data integration, implementing AI-based surveillance, establishing a specialised capital market court, and strengthening investor education. The study concludes that combining regulatory improvements, adaptive enforcement, and public legal empowerment is essential to safeguard investors, maintain market integrity, and promote sustainable economic growth.